EVALUATION OF COLE VALUE, ACIDITY AND TEXTURE OF ULTISOLS AND INCEPTISOLS IN SIBORONG-BORONG DISTRICT - Kemala Sari Lubis; Julia Sadarita Nababan (UIN Sunan Gunung Djati Bandung, 2026)
Identification of capacity of linearity and extensibility of clay, soil acidicity and texture of agricultural soils is very important because these properties are related to the estimation of soil fertility potential. This study aims to know the distribution of values of COLE, soil acidicity and texture in Ultisols and Inceptisols from Siborong-Borong district, North Tapanuli Regency, North Sumatra Province. This research was conducted by using descriptive quantitative method and soil sampling are taken by random sampling technique at 0 - 20 cm and 20 - 40 cm dept (32 samples). Parameters were analyzed consist of soil COLE value, soil acidicity and texture. The results of the analysis of Ultisol and Inceptisol soil at a depth of 20 and 40 cm show that the COLE value is classified as low to medium, ranging from 0.02 to 0.06. Soil texture are loam, sandy loam and clayey sand with a clay content of < 15%. The soil pH (acidity) value is 4.75-5.91 with the criteria of acidic and slightly acidic.